PERANAN PESANTREN DALAM MENGHADAPI GENERASI ALFA DAN TANTANGAN DUNIA PENDIDIKAN ERA REVOLUSI INDUSTRI 4.0 - Kardila Wati; Mawardi Lubis; Ahmad Walid (Attadib: Journal of Elementary Education, 2021)
Technological advances that occur at this time from time to time accumulatively have encouraged the industrial revolution and this generational difference requires the world of education to improve its quality system dynamically. To find out and describe the characteristics of prospective students of the alpha generation, boarding schools in the industrial revolution 4.0 era (challenges and opportunities for boarding schools in the industrial revolution 4.0 era), the role of pesantren in the industrial revolution 4.0 era. The type of research used is library research (Librany Research) with qualitative methods. The results of this study serve as a new discourse in making movements for educational change in the era of the industrial revolution 4.0